STRATEGI GURU PAI DALAM MENGOPTIMALKAN MASJID SEBAGAI SARANA PEMBINAAN KEAGAMAAN SISWA DI SMK MUHAMMADIYAH 06 MEDAN - Muhammad Syahril; Nurman Ginting (JURNAL TARBIYAH, 2024)
This research discusses the strategic approach applied by Islamic Religious Education subject teachers in maximizing the function of mosques as religious training centers for students at SMK Muhammadiyah 06 Medan. Based on observations and interviews, it was found that the use of mosques in this school is still limited to mandatory worship activities. PAI teachers face obstacles such as time constraints and low student interest in participating in additional religious activities. However, several innovative efforts have been made, such as regular recitations and structured character training programs at school mosques. This research uses a qualitative method with a case study approach, which involves data collection techniques in the form of observation, interviews and documentation. The research results show that with the right strategy, mosques have great potential as a means of strengthening students' character and spiritual development, especially through students active involvement in religion.